Pengembangan Augmented Reality Book Anatomi Manusia Untuk Meningkatkan Pemahaman Konsep Siswa Kelas V SD - Saputra, I Ketut Tunas Alit; Subawa, I Gede Bendesa; Andayani, Made Susi Lissia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This research is motivated by the abstract nature of human anatomy topics in the Science and Social Sciences (IPAS) subject for fifth-grade elementary school students, as well as the limitations of concrete and interactive visual media. The objective of this study is to develop and evaluate the feasibility of an Augmented Reality-based learning medium named OrgARn to provide concrete visualizations capable of enhancing students' conceptual understanding. This study employs a Research and Development (R&D) approach using the Multimedia Development Life Cycle (MDLC) model, which includes the stages of concept, design, material collecting, assembly, testing, and distribution. Testing involved 48 respondents using the User Experience Questionnaire (UEQ) instrument and black-box testing. The results of content and media expert validations indicated a “Very High” (Highly Valid) qualification, while the user experience evaluation (UEQ) placed all dimensions in the